MOTIVASI IBU RUMAH TANGGA PADA PEMBELAJARAN AL-QUR'AN DALAM UPAYA MENINGKATKAN LITERASI AL-QUR'AN DI BANDUNG DIWEK JOMBANG - Dzikri Habib, Alfi; Ali Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the motivation of housewives in participating in Qur'anic learning as a strategic effort to improve Qur'anic literacy in Bandung Village, Diwek District, Jombang Regency. The central problem addressed revolves around the reality that despite the community's strongly religious social environment, gaps in Qur'anic reading and writing ability remain prevalent among housewives due to factors such as age, domestic responsibilities, and reluctance to resume learning. A qualitative approach with a case study design was employed. Data were gathered through participatory observation, in-depth interviews with the village head, Qur'anic teacher, group leader, and member participants, and field documentation. All data were analyzed interactively following the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. Three principal findings emerged. First, the motivation of housewives is multidimensional, integrating intrinsic drives rooted in spiritual longing to draw closer to God (taqarrub ilallah) with extrinsic drives anchored in their role as the first educational institution for their children. Second, participants' Qur'anic literacy improved significantly across three dimensions: the ability to read fluently according to tajwid rules, the capacity to understand verse content through basic tafsir, and the ability to practice Qur'anic values in daily life. Third, the synergy between strong motivation and the application of andragogical principles proved to be the key to program success, where learning that is relevant, participatory, and respectful of participants' experience succeeded in creating a sustainable learning culture at the family and community level.